Solve the equation shown

-2(6x-5)=4

1 answer

To solve the equation \(-2(6x - 5) = 4\), follow these steps:

  1. Distribute the -2: \[ -2 \cdot 6x + -2 \cdot (-5) = 4 \] This simplifies to: \[ -12x + 10 = 4 \]

  2. Next, isolate the term involving \(x\). Subtract 10 from both sides: \[ -12x + 10 - 10 = 4 - 10 \] This gives: \[ -12x = -6 \]

  3. Now, divide both sides by -12: \[ x = \frac{-6}{-12} \] Simplifying this results in: \[ x = \frac{1}{2} \]

Thus, the solution to the equation \(-2(6x - 5) = 4\) is: \[ \boxed{\frac{1}{2}} \]